Researching family narratives - Phoenix, Ann; Andrews, Molly; Brannen, Julia; Squire, Corinne (SAGE Publications, 2021)
This book guides students and researchers through the processes of researching everyday stories about families. The book enables readers to 'walk through' how to do narrative research, using practical examples drawn from different relevant research arenas: those of mothering, fathering, and being a child; historical and contemporary family practices; and family lives in the UK and India. The book takes you through examples of narrative research in different media, ranging from interviews and archives to written notes, photos, maps, and web pages. Throughout, the book addresses key areas of contemporary narrative research concern, such as different types and levels of narrative analysis; power relations within narrative research; how to use mixed qualitative approaches; ethics and reflexivity in narrative work; and how to revisit and reuse narrative data. Through its focus on families, the book brings to the fore a key area in narrative work: that of intimate relationships and the 'everyday', where personal narratives allow us to understand how people are themselves making sense of their day-to-day lives. The book's focus on families also enables it to explore the complex intersectionalities of narratives, which express and construct identities that are not just family-based, but also gendered, classed, 'raced', national, and generational--Provided by publisher.